2017
DOI: 10.1103/physrevd.96.043502
|View full text |Cite
|
Sign up to set email alerts
|

Cosmological perturbations and stability of nonsingular cosmologies with limiting curvature

Abstract: We revisit nonsingular cosmologies in which the limiting curvature hypothesis is realized. We study the cosmological perturbations of the theory and determine the general criteria for stability. For the simplest model, we find generic Ostrogradski instabilities unless the action contains the Weyl tensor squared with the appropriate coefficient. When considering two specific nonsingular cosmological scenarios (one inflationary and one genesis model), we find ghost and gradient instabilities throughout most of t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
72
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(73 citation statements)
references
References 129 publications
1
72
0
Order By: Relevance
“…Recent progresses have inspired a wave of looking for stable nonsingular bounce [13][14][15] (see also [16,17]), along the road beyond the cubic Galileon (even the Horndeski theory [18][19][20]). Moreover, the developments of scalar-tensor theory (the GLPV [21] and DHOST theory [22][23][24], the mimetic gravity [25,26]) might also be able to provide us with some chances to implement stable nonsingular cosmologies.…”
Section: Introductionmentioning
confidence: 99%
“…Recent progresses have inspired a wave of looking for stable nonsingular bounce [13][14][15] (see also [16,17]), along the road beyond the cubic Galileon (even the Horndeski theory [18][19][20]). Moreover, the developments of scalar-tensor theory (the GLPV [21] and DHOST theory [22][23][24], the mimetic gravity [25,26]) might also be able to provide us with some chances to implement stable nonsingular cosmologies.…”
Section: Introductionmentioning
confidence: 99%
“…Also, to seek for the non-Gaussian features of the primordial perturbations we can use equation (31), (32) and (40). It is important to notice that, although our model is the MDBI model, but the relations (31), (32) and (40) are applicable. This is because the MDBI model is still P (X, φ) one and the differences appear in the definitions of the slow-roll parameters and also the sound speed.…”
Section: Mimetic Dbi Modelmentioning
confidence: 99%
“…The authors of [20] have shown that by considering the direct couplings of the higher derivatives of the mimetic field to the curvature of the space-time, it is possible to overcome such instabilities in some ranges of the parameters space. For more papers on the (in)stability issue see [21,22,23,24,25,26,27,28,29,30,30,31,32].…”
Section: Introductionmentioning
confidence: 99%
“…For example, one could propose that (i) singularities are hidden by horizons (Cosmic Censorship Conjecture [10,11]) or that (ii) the theory is modified such that singularities are not allowed, e.g., bouncing universes [12], limiting curvature mechanisms [13][14][15] (for recent studies see Refs. [16,17]), usually implying that the weak energy condition is violated (see Ref. [18] for a review).…”
Section: Introductionmentioning
confidence: 99%